Telemetri Pengukuran Derajat Keasaman Secara Real Time Menggunakan Raspberry Pi - Avryan Harvyandha (Politeknik Negeri Malang, 2019)
PH is the standard value of degree of acidity expressed on a scale 0-14. PH can be influenced by several factors such as temperature and CO2. Acidification occurs because CO2 enters the liquid in the form of dissolved gas then reacts with water to form a salt in the form of carbonic acid. The acidity can be determined by measuring the pH. PH measurement is an activity to determine the value of degree of acidity. PH measurement is needed to reduce the impact on the environment because pH is closely related to pollution. However, the existing measurement tools are still manual, while real time measurement is needed so the impacts on the environment can be prevented. In this study, a system that can measure pH which is influenced by CO2 concentrations in real time was created. This system consists of CO2 sensor, pH sensor, Arduino UNO R3 and Raspberry Pi. Apart from real time, the advantage is its ability to perform data acquisition using programs written in the Python 3.x programming language, so that data can be presented in tables and heatmaps. The results of sensor readings from the microcontroller to the raspberry pi can operate properly with delivery times via USB. Overall testing the system at reading the pH value is as expected, able to read the change in pH value significantly in pH of a neutral solution (7.3) and read the change of pH value that is relatively the same after the solution is injected with CO2.